DIPLOMASI PUBLIK INDONESIA DALAM MENDUKUNG KEANGGOTAAN PENUH TIMOR LESTE DALAM ASEAN - Heriamsal, Krisman; Jekaisa , Heyna (Indonesian Journal of International Relations, 2024)
This research aims to analyze Indonesia's public diplomacy to show its commitment to supporting Timor Leste's full membership in ASEAN. Using a qualitative research approach and library study methods whose data sources are obtained through online media, books and scientific articles. This research uses the concept of public diplomacy using the communication process carried out by the government to the international community. The results of this research show that Indonesia, as one of the countries that supports and encourages Timor Leste to become a member of ASEAN, continues to make efforts, one of which is through public diplomacy. Indonesia's public diplomacy to support Timor Leste's full membership in ASEAN was carried out through grant assistance from Indonesia to the Timor Leste government in the form of capacity building activities and cultural or artistic activities at the ASEAN Summit during the period of Indonesia's chairmanship of ASEAN